Media, Structures, and Power - EDWARD A. COMOR (University of Toronto Press, 2011)
The idea for a book containing some of Robert Babe’s most influential writings emerged in 2007. Given his status as one of Canada’s outstanding social scientists, the far-reaching influence of his work, and the fact that he is now in the latter years of his career, it seemed to me that the time was right for such a collection. After meeting with Bob about the project, I approached the University of Toronto Press, who immediately endorsed it. Soon thereafter, pre-eminent scholars were asked to write introductions for each of the book’s four sections. Without reservation, the first four I asked – Sandra Braman, Robin Mansell, Paul Heyer, and Hanno Hardt – agreed to participate. From the outset, the aim of the project was to go beyond publishing a relatively one-dimensional celebratory book. Instead, Bob and I agreed that the volume should represent his life’s work; reflecting its interdisciplinary breadth. Furthermore, the readings were selected with an eye on their potential to stimulate debate. Likewise, its contributors – especially the four introduction writers – were invited to engage both Bob and prospective readers by contextualizing their assigned chapters through some amount of historical, intellectual, and critical rigour.